Ordering Polymer‐Grafted Nanoparticles at Oil–Air Interfaces under Magnetic Fields. Issue 11 (19th April 2018) - Liu, Siqi; Wang, Haoyu; Akcora, Pinar
Abstract: Polymer‐grafted magnetic nanoparticles at oil–air interfaces are examined to reveal the role of chain length and anisotropy on particle packing order in thin films. It is found that particles grafted with intermediate chain lengths and sparse grafting densities exhibit enhanced packing order with increasing magnetic field strength. Voronoi tessellation results present an increase in the cell area distribution of these samples, suggesting that chain conformations are affected. For the longest graft length, particles become more disordered under magnetic fields. It is proposed that fluctuations in the bridged chains rearrange particles into less ordered packing with field application and the mechanism of packing order differs for varying graft chain lengths. Grafting anisotropy is found to determine the spatial nanoparticle organization in assembled monolayers. Abstract : Monolayer formation of polymer‐grafted magnetic nanoparticles at oil–air interfaces is examined to reveal the impact of grafted chain length on packing order parameter. While the short grafted chains are easily compressed (left), the long grafted chains rearrange and lose their packing order (right) under applied external magnetic fields.